The communicative effectiveness of market risk disclosures in the annual report of financial firms: evidence from an understandability study - Sofri Yahya; Peter, Casson (Penerbit Universiti Kebangsaan Malaysia, 1999)
The study seeks evidence on the understandability of the textual narrative of market risk information by using the Cloze Procedure. Based on Bormuth’s 57 per cent cloze criterion reference point, the results show that the narrative is less understandable. Compared to other narrative from the same section of Management Discussion and Analysis, the market risk narrative is more difficult to understand. The implication of these results is that market risk narrative is not accessible for unsophisticated readers. In addition, firms that have a higher level of derivatives activities are found to write market risk narrative is more difficult to understand. The implication of these results is that market risk narrative is not accessible for unsophisticated readers. In addition, firms that have a higher level of derivatives activities are found to write market risk narratives in a more understandable manner than less active ones. The management of these active financial firms therefore should be more careful about their communication effectiveness. This group of firms which is also big in terms of asset size is more likely to commit resources toward presenting an understandable and effective message to intended readers